(untitled) (Jurnal Bina Praja, 2017)
The current development paradigm is still dominated by the neoclassical economic perspective which sees economic development as a mechanical and simplistic process, without the need to look at aspects of respect, protection, and fulfillment of human rights, although, human rights is the first state responsibility of government. As a result, human rights are not the focus of development policy-making. Human rights and development have a mutually reinforcing relationship that will direct the efforts towards a higher quality of development.On this basis, this study shines a spotlight and examines the management of regional development planning with a human rights basis. To get an idea of ​​the reality, researchers use three areas as a sample, namely: Batang (Central Java), Trenggalek (East Java), and Tanjungpinang (Riau Islands). Existing practices are examined with a human rights-based approach, namely: the formulation process, main content, implementation mechanisms, and protection and restoration. Furthermore, a descriptive qualitative approach is selected to describe the process, understand the nonconformities as well as identify the planning process and the implementation of the development plan. For that, primary data collection is done through interview techniques, focused discussions, and field observation. While for secondary data collection through a literature study. The study shows that the fulfillment of the right to healthcare, education, and food has become priorities in regional development planning. A more transparent and accountable planning approach also opens opportunities to make human right-based development planning as the mainstream. The prerequisites driving factors lie in the dynamics of regional regulation and the commitment of the regional heads with the vision and mission outlined in the RPJMD, including a commitment to maintain a transparent, accountable and clean bureaucracy. In conclusion, the transparent planning approach in the RPJMD needs to be balanced by using human rights standards to improve the quality of human development in the region.